Pigmentary anomaly caused by mosaic 3q22.2q29 duplication. (30th September 2022) - Martinez‐Falero, Beatriz Suarez; Koutalopoulou, Anastasia; Douglas, Andrew G. L.; Kharbanda, Mira; Collinson, Morag N.; Lotery, Andrew; Lotery, Helen
Abstract : A 39‐year‐old woman sought advice regarding potential risks to her offspring due to previous possible diagnosis of incontinentia pigmenti. She had linear hyperpigmentation along the lines of Blaschko affecting the upper and lower limbs, and skin‐coloured papules on the left palm. Ophthalmoscopy revealed hypopigmented spots in the macular region of the retina in each eye due to focal areas of depigmentation of the retinal pigment epithelium. An array comparative genomic hybridization on DNA extracted from a skin biopsy revealed a 63.63‐Mb duplication, arr[GRCh37] 3q22.2q29(134212001_197837069)x3, on the long arm of chromosome 3. This case is an example of genetic mosaicism resulting from a de novo genetic defect arising at some point in embryonic development. Click here for the corresponding questions to this CME article.